The NLR family pyrin domain containing 3 inflammasome in the mechanism of electroacupuncture: Current status and future perspectives - Yuan, Min; Wang, Dong; Yang, Jiaen; Lan, Hai (Frontiers in Aging Neuroscience, 2022)
Electroacupuncture, which is the most widely used alternative medicine treatment, has been gradually recognized for its effectiveness; however, its mechanism of action is not fully understood. The NLR family pyrin domain containing 3 (NLRP3) inflammasome is a thoroughly studied inflammasome that is closely associated with Alzheimer’s disease, spinal cord injury, and other diseases and plays an important role in the diagnosis and treatment of human immune system diseases. In recent years, some scholars have found that the NLRP3 inflammasome is a part of the mechanism of action of electroacupuncture, which has attracted further attention. In the current review, using “electroacupuncture” and “NLRP3 inflammasome” as keywords and based on the existing randomized controlled trials or clinical trials, we summarize the mechanisms of electroacupuncture targeting NLRP3 inflammasome in the treatment of different diseases and discuss how to optimize the electroacupuncture protocol to obtain thorough mechanisms of NLRP3 inflammasome in electroacupuncture and improve the level of evidence.